A responsabilidade enunciativa no gênero discursivo defesa contra a acusação e ao pedido de impeachment da ex-presidenta Dilma Rousseff - Medeiros, Maria das Vitórias dos Santos (2020)
The legal and political discursive domains present a variety of textual discourse genres. This is the case of our object of investigation: Defense to the accusation and the impeachment request of former President Dilma Vanna Rousseff, which occurred in 2016. To conduct the research, we proposed a general objective to analyze the Point of View (POV), Enunciative Responsibility (ER), and Argumentation in the defense text regarding the Complaint for Crime of Responsibility No. 1, from 2015. We established the following specific objectives: i) to identify the linguistic markers that contribute to the construction of the POV; ii) to identify the materialization of the (non) assumption of enunciative responsibility; iii) to recognize the organizers and argumentative markers that contribute to the construction of the author's POV; iv) to describe the linguistic strategies that lead to the (non) assumption of enunciative responsibility. The choice of this genre is justified by its social significance, as it involves a case that affected the country, implying political, economic, and social consequences, in addition to presenting characteristics relevant to our theoretical approach. The corpus favors the calling of different voices, often establishing the use of discursive argumentation. The research followed a qualitative methodology, of an interpretative nature, of a documentary type. Our theoretical grounding is based on the studies of Adam (2011, 2018, 2018a), which aim to study the (con)textual production of meanings in concrete texts. In this direction, among the proposed levels, we will focus on the POV, enunciative responsibility, and argumentative orientation. Dialoguing with this approach, we incorporate the studies of Rabatel (2008, 2009, 2015, 2016, 2017) regarding these categories, thus configuring an enunciative and discursive approach. Following Guentchéva (1994, 2011, 2014), we will explore the concepts of mediativity and evidentiality. The analysis of the data reveals the occurrence of the POV of L1/E1 (first enunciating speaker) in relation to enunciative responsibility in two movements: (1) the attribution, that is, the non-assumption of enunciative responsibility, and (2) the assumption of enunciative responsibility. The most evoked factors by L1/E1, the Attorney General of the Union, José Eduardo Cardoso, were: reported speech (direct and indirect), the mediative framework (second enunciators), person markers, first-person verbal expressions, modal expressions (evaluative lexemes), as well as typographical marks (in bold and italic) and graphic symbols of quotation marks. Argumentation also manifests through evaluative lexemes that reveal the position of the L1/E1. The use of these enunciative devices in the analyzed textual discourse genre reveals enunciative-argumentative positions of L1/E1 in relation to the POVs of second enunciators. This occurs in the following ways: (1) agreement, through the conjunction of the POV of L1/E1 with that of e2, and (2) disagreement, through textual devices that refute the POV of e2, thus revealing an opposing viewpoint. In conclusion, the analysis shows that the management of voices and the organization of POVs guided the construction of the argumentative perspective in defense of the accused.